املواطنة بني الواقع الغريب والرؤية اإلسالمية = Citizenship between Western reality and the Islamic vision - Al-Kharousi, Sultan; Ramdane, Tahraoui (Scientific Institute for Advanced Training and Studies, Malaysia, 2020)
Citizenship is considered as one of the most complicated sociological and political concepts, despite its importance in understanding many phenomena and political, social and cultural problems of any nation. The importance of the concept of citizenship lies in the following aspects: its connection to the relationship between the individual and the state and its reversal of the essential relationships of loyalty to the country, belonging to political groups, identity, law, rights and controls of political participation, human rights, the individual’s sense of stability, political and economic security and stability, social justice, cultural and cultural openness, the dignity of human beings, the call for freedom and equality, and the lack of comparison between rights and duties. Although the concept of citizenship appeared largely in the Greeks, discussions in various popular, official, media and academic circles still exist around it. These continuous discussions give an indication of a change in the relationship between the individual and the state, from a policy that was based on dependency and care to a philosophy based on active citizenship and participation. In light of the foregoing, the current paper seeks to trace the historical stages of the emergence of the idea of citizenship, and tries to approach the western and Islamic.